2013
DOI: 10.1007/s10637-013-0045-6
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial of AS1411 (a novel nucleolin-targeted DNA aptamer) in metastatic renal cell carcinoma

Abstract: Background DNA aptamers represent a novel strategy in anti-cancer medicine. These compounds are short sequences of DNA that have protein binding effects via shape specific recognition of a target protein in an interaction which is analogous to antibody-antigen binding. AS1411, a DNA aptamer that targets nucleolin (a protein which is overexpressed in many tumor types), was evaluated in patients with metastatic, predominantly clear-cell, renal cell carcinoma (RCC) who had failed treatment with ≥1 previous tyrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
257
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(257 citation statements)
references
References 24 publications
0
257
0
Order By: Relevance
“…The c-MYC quadruplex was recently shown to be readily taken up by cells, where it destabilizes proteins that normally bind G4DNA in the cell (72). Indeed, the G4DNA oligonucleotide AS1411 has been developed as a possible treatment for cancer (67,73). G4 structures made up of DNA and In HeLa cells, 68% of the TIA1 foci co-localize with BG4 after 2 h of H 2 O 2 treatment, and 71% co-localize after 4 h of H 2 O 2 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The c-MYC quadruplex was recently shown to be readily taken up by cells, where it destabilizes proteins that normally bind G4DNA in the cell (72). Indeed, the G4DNA oligonucleotide AS1411 has been developed as a possible treatment for cancer (67,73). G4 structures made up of DNA and In HeLa cells, 68% of the TIA1 foci co-localize with BG4 after 2 h of H 2 O 2 treatment, and 71% co-localize after 4 h of H 2 O 2 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The widely demonstrated role of NCL in tumorigenesis suggests that inhibition of its oncogenic actions reduces tumor aggressiveness (9,13,19,24,32,34,47), and several studies have proposed NCL as an ideal target for antineoplastic therapies in different solid and hematological malignancies (9,19,25,34,37,38,41,42,48,49). Given the selective presence of NCL on cancer cells and cancer-associated endothelial cells, but not on normal cells, molecules targeting NCL might represent an effective approach for the selective delivery of drugs or toxins to tumors while minimizing side effects (25,41).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that NCL inhibition by siRNAs or anti-NCL aptamers affects cell viability, proliferation, and migration (14,19,(37)(38)(39)(40)(41)(42)(43). To assess the effects of 4LB5 on cell viability and proliferation, we performed a dose-response (0.9-240 nM) experiment using the scFv on MDA-MB-231 triple-negative breast cancer (TNBC) cells at different time points (24,48, and 72 h).…”
Section: Significancementioning
confidence: 99%
“…33 The two FGFR2 mutations seen in cases 17 and 18 are identical. This mutation (p. A259V) is a confirmed somatic mutation in metastatic renal cell carcinoma 34 with a SIFT score of 0.07 and we regard it as a plausible, activating driver mutation. Finally, the ERBB2 mutation in case 14 is a previously confirmed somatic oncogenic mutation (SIFT score of 0) in breast, ovarian, and bladder carcinoma.…”
Section: Mutations In Desmoplastic Melanomamentioning
confidence: 86%